5- and 6-exocyclic products, cis-2,3,5-trisubstituted tetrahydrofurans, and cis-2,3,6-trisubstituted tetrahydropyrans via Prins-type cyclization - Chavre, Satish N.; Choo, Hyunah; Lee, Jae Kyun; Pae, Ae Nim; Kim, Youseung; Cho, Yong Seo (AMER CHEMICAL SOC, 2008)
Exocyclic proc [GRAPHICS] alkynyl alcohols with various aldehydes via Prins-type cyclization in good yields. It is of interest that synthesized 5- and 6-exocyclic vinyl cations generated as a result of Prins-type cyclization could be trapped as a vinyl triflate in CH2Cl2 to give 3-furanylidenes and 3-pyranylidenes. Those 3-furanylidenes and 3-pyranylidenes underwent hydrolysis to give the corresponding 3-acyl-substituted products having all-cis-configured isomers, such as 2,3,5-trisubstituted tetrahydrofurans and 2,3,6-trisubstituted tetrahydropyrans.
Keywords: STEREOSELECTIVE-SYNTHESIS; 2,3,5-TRISUBSTITUTED TETRAHYDROFURANS; STEREOCONTROLLED PREPARATION; SYNTHETIC ROUTES; ACID; EPIMERIZATION; DIHYDROPYRANS; CONSTRUCTION; SUPPRESSION; ALDEHYDES